A Comparison of Diagnostic Value of Pre-operative Axillary Ultrasonography with Frozen Section Pathologic Results of Axillary Sentinel Lymph Nodes - Meymand, Faridadin Ebrahimi (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Although the breast cancer mortality rate has drastically decreased, it is still the second cause of cancer-induced death among women worldwide. Biopsy and surgery of sentinel lymph nodes are utilized to assess adjacent lymph nodes. However, this procedure has several side effects. Ultrasonography has been recommended as an alternative choice for distinguishing the involvement of axillary lymph nodes in breast cancer. The present study aims to investigate the diagnostic accuracy of axillary ultrasonography in patients with breast cancer to compare the results with the sentinel lymph nodes biopsy. Method: This is a cross-sectional study conducted on the patients diagnosed with breast cancer (n = 60), referred to Afzalipour and Bahonar Hospitals, Kerman, Iran during 2015–2016. Ultrasonography was carried out using an ultrasound device with the surface probe at 10 MHz. Those patients, whose different ultrasonography parameters such as size, thickness of cortex, and thickness of modulus related to the most accessible susceptible lymph node showed no involvement, were included in the study. Sentinel lymph nodes were studied through concurrent utilization of the isotope injection method (scintigraphy) and blue iso-sulfate injection method. All samples were subjected to pathological analyses, and the results were compared to the ultrasonography results. Results: Results of permanent pathology were positive in all of the 9 patients whose Frozen Section results were positive. Of the 51 patients with negative Frozen Section results, only three demonstrated positive permanent pathologic results, and 48 participants showed negative permanent pathology. Considering the validating assessments, the negative predictive value of ultrasonography is 85%, compared with the frozen section specimens of sentinel nodes. Conclusion: Biopsy of sentinel lymph nodes could be replaced with ultrasonography only by an expert and trained radiologist. It is recommended to use a predefined protocol in collaboration with four medical groups including radiology, nuclear medicine, surgery, and pathology groups.